Characterizations of Electromagnetic Radiated Emission from Digital Electronic Circuits in Conductive Enclosure - Mustam, S.M.; Jenu, M.Z.M. (Journal of Engineering and Technology (JET), 2011)
The issue of electromagnetic compatibility compliance is crucial during the design process of digital circuit boards. This is to control the level of electromagnetic radiated emission and the products to function at satisfactory performance. Basically, an electromagnetic wave radiates whenever time varying currents flow in a circuit. Therefore, it is important to understand the basic concepts of the emission and the suitable mitigation techniques. In this paper, radiated emission measurements in a 3-meter semi-anechoic chamber for two cases of a printed circuit board design are presented and discussed. The first circuit is designed without electromagnetic compatibility consideration and the second is circuit design with electromagnetic compatibility best practices. The results show that the emission level is higher than the product standard limits due to the radiation from the circuit board itself and the interfacing cable. The level can be minimized by keeping the areas of power or signal and its return path loops smaller and the use of a short cable. This means, its behavior as efficient radiating antennas are reduced. The reduction of emission level also can be achieved by considering the employment of damping resistor and common mode chokes. Moreover, the employment of shielding enclosure provides the final option in order to achieve electromagnetic compatibility compliance.